Enhancing Pedagogical Competence in Inclusive Early Childhood Education through Interactive Digital Modules: A Pre-Experimental Study - Widiastuti, Yuanita Kristiani Wahyu; Hermanto (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
One of the primary challenges in early childhood education (ECE) is ensuring that teachers possess the necessary pedagogical competence to effectively support diverse learners, particularly in inclusive education settings where students with special needs require tailored teaching strategies. This study explores the effectiveness of interactive digital modules in enhancing the pedagogical competence of early childhood education (ECE) teachers in inclusive settings. Using a quantitative pre-experimental design, 70 teachers from 12 inclusive ECE institutions participated in pre-and post-tests to assess their pedagogical skills before and after module exposure. Results show a significant increase in post-test scores, with an average improvement from 50 to 89, confirmed by a paired sample t-test (p < 0.01). The N-Gain analysis revealed a high level of effectiveness, with an average score of 0.78, indicating that the modules substantially improved teacher competencies. However, the lack of a control group limits the study’s ability to attribute improvements solely to the intervention. Other factors, such as previous teaching experience or additional resources, may have influenced the outcomes. Despite this limitation, the findings suggest that interactive digital modules are valuable for advancing pedagogical skills in inclusive education. These results have important implications for teacher professional development, supporting integrating of digital tools into ECE teachers' training programs. Future research should employ more rigorous experimental designs, including control groups, to better isolate the impact of digital modules and investigate their long-term effects on teaching competence and student outcomes in inclusive environments.